XML editor for UNIMARC and MARC 21 cataloguing. - Dimic B; Surla D (Electronic Library, 2009)
Purpose -- The purpose of this paper is to model and implement an extensible markup language (XML)-based editor for library cataloguing. The editor model should support data input in the form of free text with interactive control of structure and content validity of records specified in the UNIMARC and MARC 21 formats. The editor is implemented in the Java programming language in the form of a software package. Design/methodology/approach -- The unified modelling language (UML 2.0) is used for the specification of both the information requirements and the model architecture. The object oriented methodology is used for design and implementation of the software packages, as well as the corresponding CASE tools. Findings -- The result is an editor for UNIMARC and MARC 21 cataloguing. The editor is based on the XML technologies by which the two basic characteristics are achieved as follows: a possibility of integrating the editor into different library software systems and, moving to another format requires only the changes of the module for bibliographic record data control. Research limitations/implications -- A basic limitation of the system is related to the subsystem that controls validation of the bibliographic records and its expansion for work with other bibliographic formats. In the proposed solution, a part of the control of data input is included into the implementation itself and it is related to the UNIMARC format. That is, a part of data by which the control is done, such as repeatability of the record elements and the codebooks, is contained in the XML document of the format that is input information in the editor. However, the control that is related to validation of the format of content in record elements cannot be performed for any other format without modification in the implementation. Therefore, the research could be continued by considering the separation of data used for content control as input information for the application. In that way, this segment would also become implementation independent. One of the solutions should be extending the XML document of the format by this data. Some other solution should mean creating a totally separate system for the content validation. Moreover, the proposed editor supports processing of a bibliographic record only in the UNIMARC and MARC 21 formats. Processing of records in other formats requires considerable changes in the model. Practical implications -- The model of a new editor is developed on the basis of the experience and needs of electronic management in city and special libraries. Based on the given model a new editor is implemented and integrated into the BISIS software system used by the mentioned libraries. Testing and verification are performed on the bibliographic records of the public city libraries. Originality/value -- The contribution of this work is in the system architecture that is based on the XML documents and is independent of the bibliographic format. The XML document that contains data about the bibliographic format represents the editor input information. After a bibliographic record is created in this editor, the record is stored into an XML document that represents the editor output information. This XML document can be stored into various software systems for data storage and retrieval.